2019
DOI: 10.1029/2018ms001538
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Neodymium Isotopes in the Ocean Component of the Community Earth System Model (CESM1)

Abstract: Neodymium (Nd) isotopic composition (εNd) is an important tracer for water mass mixing and the reconstruction of past ocean circulation. To allow for a direct model‐data comparison, we have implemented Nd isotopes in the ocean component of the Community Earth System Model (CESM1.3). The model is able to capture the major features of the observed modern distribution of both εNd and Nd concentrations. Our model provides a useful tool for the interpretation of εNd reconstructions. For example, we show that in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
83
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(95 citation statements)
references
References 59 publications
11
83
0
1
Order By: Relevance
“…Part of the smaller mismatch found here (5.3 pmol/kg) can be attributed to the exclusion of seawater data from the uppermost 250 m in our approach. Even when considering all water depths including near‐surface water, the misfits remain smaller than listed by Rempfer et al (2011) and Gu et al (2019) (6.5 pmol/kg; Table S3). Both previous studies reported particularly large deviations in the top 2,000 m of the water column, due to too low Nd concentrations at these depths in the models compared to modern seawater.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Part of the smaller mismatch found here (5.3 pmol/kg) can be attributed to the exclusion of seawater data from the uppermost 250 m in our approach. Even when considering all water depths including near‐surface water, the misfits remain smaller than listed by Rempfer et al (2011) and Gu et al (2019) (6.5 pmol/kg; Table S3). Both previous studies reported particularly large deviations in the top 2,000 m of the water column, due to too low Nd concentrations at these depths in the models compared to modern seawater.…”
Section: Discussionmentioning
confidence: 64%
“…The steady-state AMOC strength simulated in the Bern3D model under preindustrial boundary conditions is 17.7 Sv (Sv: Sverdrup = 10 6 m 3 /s), which agrees well with modern observations (e.g., Frajka-Williams et al, 2019), however, with NADW slightly shallower in the model than observed in the modern ocean ( Figure 4). As reported by previous studies (Gu et al, 2019;Rempfer et al, 2011), the MAEs of the Nd concentration and ε Nd cannot be minimized with the same set of parameters ( Figure S4). Therefore, we choose the following parameters in between the two minima as a compromise: a benthic Nd flux of 3.3 × 10 9 g/a corresponding to 5.4 pmol/(cm 2 a), a scavenging efficiency parameterized by the ratio of particulate to dissolved Nd concentration of 0.0014 (see Rempfer et al, 2011), and a riverine Nd scaling of 3.5 (corresponding to an increase of all riverine Nd fluxes by a factor of 3.5), yielding a mean Nd residence time of 690 years.…”
Section: Bern3d Control Simulation and Sensitivity Testsmentioning
confidence: 68%
See 3 more Smart Citations